Reforestation of the Rehabilitation Zone of Mutis Timau National Park to Enhance the Regeneration of Ampupu (Eucalyptus urophylla) - Lusia Sulo Marimpan; Tomycho Olviana; Nixon Rammang; Roni Haposan Sipayung; Ayuvera Rifani Ray (Ali Institute of Research and Publication, 2026)
Mutis Timau National Park is the newest national park designated in East Nusa Tenggara and was declared the 56th national park in Indonesia on 8 September 2024 by the Ministry of Environment and Forestry. Located across South Central Timor, North Central Timor, Kupang, and Belu Regencies, and partially bordering Timor-Leste, this area is widely known as the “Mother of Timor Island.” Ampupu (E. urophylla), a drought-adapted and fire-resistant species, dominates this region; however, its natural regeneration has continued to decline. This community service activity aimed to support the conservation and regeneration of Ampupu through reforestation in the rehabilitation zone using native species, namely naturally growing seedlings collected from their original habitat. Prior assessment of site conditions and previous research in the area supported the selection of this approach. A total of 100 Ampupu seedlings were planted and maintained intensively, resulting in a survival rate of 89%. The high survival rate was supported by the use of locally sourced seedlings, which required minimal adaptation, and by intensive maintenance, including the installation of supporting stakes to protect seedlings from livestock grazing in the forest area. In the short term, reforestation can increase stand productivity, while in the long term, it can enhance the forest’s capacity to store carbon and absorb CO₂ emissions.